Providing a Regional Policy-Making Ecosystem Model for the Ministry of Health and Medical Education of Iran - Mohammadpoor Fallah Nyakoyi, Seyed Ashraf; Hashemi, Seyed Hamed; Sorati, Poran (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this study was to provide a regional policy-making ecosystem model for the Ministry of Health and Medical Education of Iran.Methodology: The research method was descriptive-analytical, with an applied nature. The statistical population of this study consisted of experts in the Ministry of Health and Medical Education. Considering the type of research, 20 individuals with master's and doctoral degrees and more than five years of experience in this field were purposefully sampled and selected. Data collection was conducted using field methods, including interviews and questionnaires. The obtained data were analyzed using interpretive structural modeling.Findings: The findings indicated that 12 factors were identified as part of the regional policy-making ecosystem for the Ministry of Health and Medical Education of Iran. The (process value network) was identified as the most influential component of the regional policy-making ecosystem for the Ministry of Health and Medical Education of Iran. Following this, the factors of (sustainable development) were identified, with (resource management and monitoring and evaluation) in the third level, (current situation analysis) at the second level, and finally (coordination and cooperation, infrastructure and technology, public participation, international cooperation, national policies, and process achievements) occupying the first level.Conclusion: Therefore, it can be concluded that these factors influencing the regional policy-making ecosystem for the Ministry of Health and Medical Education of Iran may lead to further development and success of this organization